A Review Of Reverse Osmosis Membrane Fouling: Formation and Control - Rizka Mulyawan; Agam Muarif (Master Program of Information Technology, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
Membrane application in reverse osmosis (RO) membrane is getting more attention especially in producing drinking water. However, RO membrane faces challenges that reduces its performance such as its permeation flux, salt rejection, additional energy demand, lifetime decrease, extra pre-treatment process, cleaning and maintenance. The challenge is the formation of fouling. RO membrane fouling can happen inside or outside the membrane and the characteristics of membrane fouling differs from one type to other types, depending on the nature and location of membrane fouling. There are several types of RO fouling, which are Biofouling, Organic Fouling, Inorganic Fouling and Colloidal Fouling. The causes of RO membrane are different from one to another. The properties and materials of the solution entering RO membrane are important as it affects the type of fouling of RO membrane fouling. All of the RO membrane foulings need to be considered during membrane usage and demand solution to be controlled. In order to control the fouling in Reverse Osmosis membrane, there have been several control solutions discovered to the membrane fouling challenges. The control solutions are specified to each one of the fouling, in spite of wide applications for some of it. The control solutions are pre-treatment, which has many methods such as photo oxidation, coagulation, scale inhibitor, ion exchange resins, granular media and membrane treatment, membrane monitoring, membrane cleaning, surface modification, and material addition to membrane or novel membrane material. With various control solutions discovered, the RO membrane still faces fouling issue and is still demanding some more advanced applicable control solutions.